Are high performance work systems compatible with the extending working life agenda?. Issue 1 (27th January 2021) - Haile, Getinet
Abstract : Purpose: The paper examines the compatibility of two UK policy priorities – extending working life (EWL) and the promotion of national economic performance through high performance work practices (HPWP). Design/methodology/approach: Empirical analysis has been conducted using data from WERS2011 to test hypotheses on whether age moderates the link between HPWP and employee well-being outcomes. Findings: Development-oriented human resource strategies are found to compromise the wellbeing of older workers relative to younger ones, while some dimensions of HPWP lead to more favourable wellbeing outcomes for older workers relative to their younger counterparts (flexible working, performance-related pay and appraisal systems). Research limitations/implications: At older ages those still in the workforce may be over-represented by happier and psychologically more robust individuals who have settled into jobs they find fulfilling, matching their personal characteristics and abilities. If so, the adverse well-being influence of development-oriented strategies may be understated, while favourable well-being outcomes for older workers may be overstated. Practical implications: HRM strategies may need to be more age sensitive to support the EWL agenda better. Originality/value: While many studies have examined the link between HPWP and a range of individual-level outcomes, less widely researched is whether responses vary by age, which the paper addresses.